Konflik Muslim Rohingya dalam Bingkai Tiga Media Islam di Indonesia - Anggi Septa Sebastian; Iwan Awaluddin Yusuf (Program Studi Ilmu Komunikasi, 2013)
Rohingya Case in Myanmar attracted the attention for a number of Islamic media in Indonesia, including eramuslim.com site, Republika daily and Sabili magazine. Although all three of Islamic media covering the same case, and even with the same sources, but there are striking differences between all of them. eramuslim.com framing the case as a case of violence involving name of religion. Republika daily saw this case as a organized violation of the law until to be a problem that also resolved by the Non-Aligned Movement. While the Sabili magazine saw as injustice in making policies by Myanmar government that make an oppressed Rohingya by various sides.